Ermittlung der Einwohnerzahl im Zensus 2022 - Corinna Bretschi; Steffen Seibel; Ingeborg Vorndran; Miriam Pfahl (WISTA - Wirtschaft und Statistik, 2024)
Wesentliches Ziel eines Zensus ist die Ermittlung der Einwohnerzahlen für Bund, Länder und Gemeinden. Der Zensus 2022 wurde wie bereits der Zensus 2011 regis- tergestützt durchgeführt. So basiert die Ermittlung der Einwohnerzahl auf den Melde- registern. Diese wurden jedoch nicht einfach ausgezählt, sondern es gab noch eine Reihe ergänzender und korrigierender Maßnahmen - teils innerhalb der Daten aus den Registern, teils durch zusätzliche primärstatistische Erhebungen. Der Beitrag stellt die einzelnen Schritte der Einwohnerzahlermittlung im Zensus 2022 vor. – – A primary objective of a census is to establish population counts for Germany, the Länder and the municipalities. The 2022 Census was conducted as a register-assisted census of the population, as was the 2011 Census. Population figures were therefore determined on the basis of the population registers. The entries in these registers were not simply counted, however; instead, a number of supplementary and corrective measures were also implemented, with some applying directly to the data from the registers and some involving additional primary data surveys. This article explains the individual steps involved in counting the population in the 2022 Census.
Keywords: 519; Registergestützter Zensus; Melderegister; Mehrfachfallprüfung; Haushaltebefragung; Referenzdatenbestand; register-assisted census; population register; check for multiple registration; household survey; stock of reference data